Seed-Borne Mycoflora of Seven Tomato Cultivars From Oyo and Kaduna States in Nigeria. - Otusanya, M. O. (European Journal of Applied Sciences, 2022)
Seven tomato seed cultivars from Oyo and Kaduna States in Nigeria that had been stored for various periods were treated with and without surface-sterilization for seed-borne fungi. The experiment was completely randomized design with five replicates per cultivar and fifty seeds per replicate, using blotter method. The seeds were incubated under an alternating cycle of 12 hours near ultra-violet light and 12 hours darkness for seven days. Germination counts after the incubation were 20.40% to 76.40%. On the surface –sterilized seeds, Aspergillus flavus and Fusarium moniliforme ranked first in dominance, following (second) were Aspergillus niger and Curvularia pallescens and third was Cocliobolus lunatus. Ranking fourth were Fusarium solani, Thielavia terricola and Verticillium sp. Eight fungi namely Aspergillus terreus, Cercospora sp. Curvularia senegalensis, Fusarium equiseti, Fusarium pallidoroseum, Pitomyces chartarum, Trichoderma sp. and Trichothecium sp., each occurred only on one cultivar. Pitomyces chartarum, Thielavia terricola and Trichothecium are new records of seed-borne fungi of tomato in Nigeria. External contaminants on seeds that were not surface-sterilized were Chaetomium nigricolor, Choanephora sp. Cladosporium sp. Penicillium sp., Phoma sp. and Rhizopus nigricans. Seed-borne fungi as agents of disease, seed treatment with Bioagents or Antagonistic microbes as a vital or compulsory step in tomato crop improvement which is eco-friendly and enhancing crop development, as well as emphasis to curtail the species of the Aspergilli that have inhibited maximum yield potential of tomato for some decades in South West Nigeria is discussed.